Adaptive resistance of melanoma cells to RAF inhibition via reversible induction of a slowly dividing de‐differentiated state. Issue 1 (9th January 2017) - Fallahi‐Sichani, Mohammad; Becker, Verena; Izar, Benjamin; Baker, Gregory J; Lin, Jia‐Ren; Boswell, Sarah A; Shah, Parin; Rotem, Asaf; Garraway, Levi A; Sorger, Peter K
Abstract: Treatment of BRAF ‐mutant melanomas with MAP kinase pathway inhibitors is paradigmatic of the promise of precision cancer therapy but also highlights problems with drug resistance that limit patient benefit. We use live‐cell imaging, single‐cell analysis, and molecular profiling to show that exposure of tumor cells to RAF/MEK inhibitors elicits a heterogeneous response in which some cells die, some arrest, and the remainder adapt to drug. Drug‐adapted cells up‐regulate markers of the neural crest (e.g., NGFR), a melanocyte precursor, and grow slowly. This phenotype is transiently stable, reverting to the drug‐naïve state within 9 days of drug withdrawal. Transcriptional profiling of cell lines and human tumors implicates a c‐Jun/ECM/FAK/Src cascade in de‐differentiation in about one‐third of cell lines studied; drug‐induced changes in c‐Jun and NGFR levels are also observed in xenograft and human tumors. Drugs targeting the c‐Jun/ECM/FAK/Src cascade as well as BET bromodomain inhibitors increase the maximum effect ( E max ) of RAF/MEK kinase inhibitors by promoting cell killing. Thus, analysis of reversible drug resistance at a single‐cell level identifies signaling pathways and inhibitory drugs missed by assays that focus on cell populations. Synopsis: Responses of BRAF V600E melanoma cells to vemurafenib were studied at the single‐cell level using live‐cell imaging and by transcriptional and biochemical profiling to uncover a slowly dividing, de‐differentiated cell state associated with drug resistance but inhibitable by drug combinations. Cell‐to‐cell variability in BRAF V600E melanomas generates drug‐tolerant subpopulations. The drug‐tolerant, slowly dividing NFGR High state is transiently heritable. Drugs against a proposed c‐Jun/ECM/FAK/Src cascade block acquisition of this phenotype. The NGFR High drug‐tolerant state is also blocked by BET inhibitors in vitro and in vivo . Drugs that block adaptation by cell subpopulations increase cell killing by RAF/MEK inhibitors. LINCS‐compliant data and methods are freely available to enhance reproducibility. Abstract : Responses of BRAF V600E melanoma cells to vemurafenib were studied at the single‐cell level using live‐cell imaging and by transcriptional and biochemical profiling to uncover a slowly dividing, de‐differentiated cell state associated with drug resistance but inhibitable by drug combinations.